1963
DOI: 10.1002/cber.19630960321
|View full text |Cite
|
Sign up to set email alerts
|

Versuche im Enamingebiet, VII. Reaktionen von Arylsulfonylaziden mit Enaminen aus Ketomethylenverbindungen

Abstract: Arylazide, die im Ring elektronenanziehende Gruppen enthalten (wie zum Beispiel 2.4-Dinitro-phenylazid), oder Arylsulfonylazide reagieren gleichfalls auch bei 0" mit den Enaminen energisch nach Schema B : Unter N2-Abspaltung entstehen Umlagerungsprodukte der infolge ihrer Unbestiindigkeit nicht isolierbaren Addukte.Vorliegende Mitteilung befal3t sich mit zwei unerwarteten Umsetzungen zwischen einigen Enaminen und Arylsulfonylaziden.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
40
0
1

Year Published

1963
1963
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(42 citation statements)
references
References 6 publications
1
40
0
1
Order By: Relevance
“…Moriarly, and K. K. A later interpretation [138], according to which the adduct contains a Cmembered ring, is less convincing; nevertheless, the structure proposed by Beckmann requires further confirmation. The exothermic reactions of C,N-diphenylnitrone, C-phcnyl-N-methylnitrone, and 3,4-dihydroisoquinoline-N-oxide with phenyl isocyanate yield, respectively, 8 I %, 94 x, and 96 % of the crystal-line adducts [116]. A 1: 1 adduct obtained from Cphenyl-N-methylnitrone and phenyl isothiocyanate is presumably 2-methyl-3,4-diphenyI-1,2,4-0xadiazolidine-Sthione (83) 11161. from C,N.diphenylnitronc and allyl alcohol.…”
Section: ~C1c61i4-cliomentioning
confidence: 99%
“…Moriarly, and K. K. A later interpretation [138], according to which the adduct contains a Cmembered ring, is less convincing; nevertheless, the structure proposed by Beckmann requires further confirmation. The exothermic reactions of C,N-diphenylnitrone, C-phcnyl-N-methylnitrone, and 3,4-dihydroisoquinoline-N-oxide with phenyl isocyanate yield, respectively, 8 I %, 94 x, and 96 % of the crystal-line adducts [116]. A 1: 1 adduct obtained from Cphenyl-N-methylnitrone and phenyl isothiocyanate is presumably 2-methyl-3,4-diphenyI-1,2,4-0xadiazolidine-Sthione (83) 11161. from C,N.diphenylnitronc and allyl alcohol.…”
Section: ~C1c61i4-cliomentioning
confidence: 99%
“…First, we prepared the bromo-substituted 1-aryl-1,2,3-triazoles 1-7 by reaction of bromophenyl azides with -dicarbonyl compounds using a reported procedure (Scheme 2) [29].…”
Section: Resultsmentioning
confidence: 99%
“…Evidently, the primary [3 2] cycloadduct, the dihydrotriazole 3c, underwent a spontaneous cycloreversion under the condition of reaction to furnish diazomethane and the carboximidamide 5. This behavior, which is attributed to the strongly electronwithdrawing character of the tosyl group, is well known from the reaction of simple enamines with arenesulfonyl azides, and the mechanism has been studied [9]. In the reaction of phenyl azide (2d) with 1, dihydrotriazole 3d could not be isolated either because it underwent spontaneous elimination of morpholine producing triazole 4d.…”
mentioning
confidence: 96%
“…While enamines have been recognized as dipolarophiles par excellence for [3 2] cycloadditions with aryl and arylsulfonyl azides since the early investigations of Fusco et al [9] and the kinetic studies of Huisgen et al [6], conjugated enamines, i. e., 1-amino-and 2-amino-1,3-dienes, have been somewhat neglected in this respect. Bianchetti et al have reported that 1,4-dialkyl-substitued 2-morpholinobuta-1,3-dienes [10] and a 2-morpholinocyclohexa-1,3-diene derivative [11] react with 4-nitrophenyl azide and p-toluenesulfonyl azide in much the same manner as simple enamines.…”
mentioning
confidence: 99%